THE EFFECT OF SLUDGE ON GROWTH AND YIELD OF PLANT EGGPLANT ON ALLUVIAL SOIL - PAULUS, SITO; Sulistyowati, Henny; Mulyadi, Ahmad (Jurnal Sains Pertanian Equator, 2018)
This research aims to obtain the best dose of sludge on the growth and yield of plant eggplant in alluvial soil. The research was conducted at Parit Haji Husin 1 street, Sejahtera narrow street, Bangka Belitung Laut Village, Pontianak Southeastern District, Pontianak City for about 4 months starting from March 18th until July 7th, 2017. The design used in this research was Completely Randomized Design consisting of five treatment dose of sludge, four replicates, and four sample plant. The treatment in mean here is 180 g sludge/polybag, 540 g sludge/polybag, 900 g sludge/polybag, 1.260 g sludge/polybag, and 1.650 g sludge/polybag. The variables observed in this research is height plant, volume roots, weight dry plant, amount of fruit plant, weight fruit per plant, weight per fruit, length fruit, and diameter of fruit. The research results show that sludge influential real to height plant, weight dry plant, and length fruit, and influential not real to volume roots, amount of fruit plant, weight fruit per plant, weight per fruit, and diameter of fruit. Based on the result of the research it can be concluded that the giving of sludge with dose of 900 g/polybag or equal to 25 ton/ha is an dose effective for the growth and yield of plant eggplant in alluvial soil.